Development of Analytical Thinking in Future History Teachers - Mansurjonovna, Mirzaahmedova Gulshanoy (Researchparks Publishing, 2023)
An important aspect of teacher competence is analyzing complex classroom situations and suggesting appropriate actions that follow from the analysis. Novice teachers’ analyses are, however, typically simpler than analyses done by experienced teachers. The aim of this study was to investigate whether the analytical skills of pre-service teachers had developed throughout teacher education, and whether the pattern of strengths and weaknesses in students’ performances during their first semester had changed at the time of graduation. The results show that the skills did not improve during teacher education, since the students performed at the same level during the first and the last semester.